Health Literacy Concepts, Themes, and Research Trends Globally and in Latin America and the Caribbean: A Bibliometric Review - Paucar-Cáceres, A.; Vílchez Román, C.; Quispe-Prieto, S. (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
(1) Background: Health literacy (HL) debates have increased significantly in the last two decades. HL concepts/themes and models have achieved substantial development in the US and Europe. Although there have been some efforts to develop HL in Latin America and the Caribbean (LAC), these seem to be few and scattered. This paper reviews and discusses developments of HL concepts and themes globally and in LAC over the last two decades. (2) Purpose: This study aimed to identify the prevalent health literacy concepts/themes deployed globally and in LAC as reported in academic journals from 2005 to 2022. We looked into which fields of knowledge have been informing HL research over the last decades. (3) Methods: We conducted a structured search on the Web of Science (WoS), Scopus, PubMed, and SciELO databases to extract the textual data for bibliometric analysis. We analyzed the textual data with VOSviewer and Biblioshiny to better understand health literacy themes and strands currently being researched in the LAC region. We conducted the searches in two periods: the first in May 2023 and the second in October 2023. (4) Results: The bibliometric study highlighted five WoS categories informing most HL global studies: (i) public environmental occupational health; (ii) environmental sciences; (iii) health policy services; (iv) health care science services; and (v) communication. The two predominant categories in LAC are public environmental occupation health and health policy services. Journals hosting HL publications come from these WoS categories. Themes in HL publications can be organized into four thematic clusters: (i) analytical (research designs, analytic techniques, and criteria for examining HL data); (ii) psychometric (measurement properties of data collection tools); (iii) pragmatic (practical issues related to implementing HL programs); and (iv) well-being (effectiveness of HL programs on mental health and illness treatment). (5) Conclusions: There is expanding interest in health literacy among scholars. The number of publications has increased substantially, particularly over the last five years. These are dominated by the Global North. The metrics show that LAC and Africa are trailing in publications. There is an emerging focus on adult literacy, functional/low health literacy, and their effect on improving capabilities, comprehension, and communication regarding health-related topics.
Keywords: Health literacy; Scopus; Latin Americans; Public health; Library science; Thematic analysis; Bibliometrics; Literacy; Political science; MEDLINE; Health care; Medicine; Social science; Sociology; Qualitative research; Computer science; https://purl.org/pe-repo/ocde/ford#5.02.00